Answer:
C)3x+6y=9
-2x-4y=4
Explanation:
A student took a system of equations, multiplied the first equation 2 by 3 and the second equation by , then added the results together.
Lets check with each option
We multiply the first equation by 2 and second equation by 3 and add it.
When both x and y terms gets cancelled then we can say there were no solutions.
A) -2x+4y=4
-3x+6y=6
Equation becomes
-4x + 8y = 8
-9x + 18y = 18
------------------------
-13x + 26y = 26
B) 3x+y=12
-3x+6y=6
Multiply first equation by 2 and second equation by 3
6x + 2y = 24
-9x + 18x = 18
------------------------
-3x + 20y = 42
C)3x+6y=9
-2x-4y=4
Multiply first equation by 2 and second equation by 3
6x + 12y = 18
-6x - 12y = 12
---------------------------
0 = 30
Both x and y terms becomes 0. Hence there is no solution for these system of equations.